The Role of Work Engagement in Mediating Job Stress and Religiousness on Subjective Well-Being at Secondary Education Institutions in Medan City - Kesuma, Indra; Zainuddin, Zainuddin; Sofiyan, Sofiyan; Faris, Salman (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This study supposed to determine the role of work engagement in mediating job stress and religiosity towards subjective well-being at senior secondary education institutions in Medan City. The research method that will be used in this research is an associative method with a quantitative approach. In this study, the population and saturated samples taken were all teachers in 6 private universities in Medan City, totaling 333 respondents. The analysis model using structural equation modeling (SEM) is a collection of statistical techniques that allow testing a series of relatively complex relationships simultaneously. The results showed that directly job stress has no effect and is not significant on the work engagement of teaching staff at secondary education institutions in Medan. Directly job stress has no effect and is not significant to the subjective well being of teaching staff secondary education institutions in Medan. Directly religiosity has a significant effect on the work engagement of teaching staff at secondary education institutions in Medan. Directly work engagement has a significant effect on the subjective well being of teaching staff at secondary education institutions in Medan. Indirectly, work engagement does not moderate job stress on the subjective well being of teaching staff at secondary education institutions in Medan. Work engagement indirectly moderates religiosity on the subjective well being of teaching staff at secondary education institutions in Medan.